2014
DOI: 10.1371/journal.pone.0107990
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant p35 from Bacteria Can Form Interleukin (IL-)12, but Not IL-35

Abstract: The Interleukin (IL)-12 family contains several heterodimeric composite cytokines which share subunits among each other. IL-12 consists of the subunits p40 (shared with IL-23) and p35. p35 is shared with the composite cytokine IL-35 which comprises of the p35/EBI3 heterodimer (EBI3 shared with IL-27). IL-35 signals via homo- or heterodimers of IL-12Rβ2, gp130 and WSX-1, which are shared with IL-12 and IL-27 receptor complexes, respectively. p35 was efficiently secreted in complex with p40 as IL-12 but not with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 34 publications
(72 reference statements)
0
30
0
Order By: Relevance
“…and more rigorous studies are needed to fully understand the different receptor complexes and the signal transduction of the cytokine IL-35. Biochemical analysis are further complicated by the fact that p35 protein produced in bacteria can be used to assemble IL-12, but not IL-35 [45].…”
Section: Plasticity Of Gp130 and Il-6rmentioning
confidence: 99%
“…and more rigorous studies are needed to fully understand the different receptor complexes and the signal transduction of the cytokine IL-35. Biochemical analysis are further complicated by the fact that p35 protein produced in bacteria can be used to assemble IL-12, but not IL-35 [45].…”
Section: Plasticity Of Gp130 and Il-6rmentioning
confidence: 99%
“…So far, only the anti-inflammatory property is known for IL-35; therefore, this cytokine could be one of the most promising candidates for clinical application against allergic and autoimmune diseases. However, among the IL-6/IL-12 family cytokines, IL-35 is considered to differ from the other cytokines (75). Although bacterially produced and purified recombinant proteins of EBI3 and p35 were correctly folded and biologically active in combination with p28 and p40, respectively, no biologically active IL-35 was reported to be formed when the p35 and EBI3 were combined (75).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, among the IL-6/IL-12 family cytokines, IL-35 is considered to differ from the other cytokines (75). Although bacterially produced and purified recombinant proteins of EBI3 and p35 were correctly folded and biologically active in combination with p28 and p40, respectively, no biologically active IL-35 was reported to be formed when the p35 and EBI3 were combined (75). There are currently no reasons to explain this, but IL-35 might need additional, yet unidentified, molecules for efficient secretion and exertion of biological activity (75).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Through different subunit pairing especially in the IL-12 family EBI3 as well as p28 are used by different cytokines. EBI3 can form the cytokine IL-35 by binding the IL-12 subunit p35 [15,16], although the interaction site seems to be very unconventional in the context of this cytokine family [17]. For p28 it was shown that the site II binding to the cytokine binding module (CBM) of different cytokine b-receptors is depending on the bound a-receptor, in this case EBI3 or the IL-6R, which results in the activation of a gp130/WSX-1 heterodimer by IL-27 and the activation of a gp130 homodimer by p28 through the IL-6R [10].…”
Section: Expression Of Interleukin-27 and Its Receptorsmentioning
confidence: 99%